"Influencia de la temperatura y la agitación del medio corrosivo constituido por h2so4-0.5 m y hcl-0.5 m, sobre la velocidad de corrosión del acero astm a335 p22, medido mediante diferentes técnicas electroquímicas” - Guevara Reyes, Yuvi (2014)
ASTM A335 Steel grade P22 is widely employed for boiler tubing and steam piping in thermal power plants. Scale formation in internal surface of boiler tubes is one of the major problems in most of high-pressure boilers of thermal power stations. Two major problems result from deposit fouling on the interior tube surface: (1) Loss of heat transfer, and (2) Under-deposit corrosion. Therefore, it is necessary to clean, and mineral acids are typically employed for this purpose. The present study addresses the corrosion behavior of ASTM A335 P22 steel in hydrochloric and sulfuric acid solution at different temperature and agitation using different technique electrochemical. The relationship between the rate of corrosion on P22 steel and the temperature of the acid medium follows the Arrhenius kinetic model. The increase of the temperature and agitation of the acid medium produced on the surface of the P22 steel a depolarization of the reaction of hydrogen evolution, which contributes to the increase in the rate of corrosion. Also, the corrosion rate of P22 steel in H2SO4 -0.5M is much greater than in HCl-0.5M, so that the acid cleaning process for boiler components made of P22 steel be satisfactory, when performed with HCl without stirring (method of filling and soaked) at room temperature; should avoid using H2SO4 due to its high corrosivity.